Pericardial tamponade as a complication of invasive cardiac procedures: a review of the literature - Adamczyk, Maria; Wasilewski, Jarosław; Niedziela, Jacek; Rozentryt, Piotr; Gąsior, Mariusz (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2019)
Cardiac tamponade (CT) is a rare but often life-threatening complication after invasive cardiac procedures. Some procedures favor CT. Furthermore, the incidence depends on patients’ comorbidities, sex and age and operators’ skills. In this paper we review studies and meta-analyses concerning the rate of iatrogenic CT. We define the risk factors of CT and show concise characteristics for each invasive cardiac procedure separately. According to our analysis CT occurs especially after procedures requiring transseptal puncture or perioperative anticoagulation. The overall rate of CT after such procedures varies among published studies from 0.089% to 4.8%. For this purpose we searched the PubMed database for clinical studies published up to December 2018. We included only those studies in which a defined minimum of procedures were performed (1000 for atrial fibrillation ablation, 6000 for percutaneous coronary intervention, 900 for permanent heart rhythm devices, 90 for left atrial appendage closure, 300 for transcatheter aortic valve implantation and percutaneous mitral valve repair with the Mitra-Clip system). The search was structured around the key words and variants of these terms. In addition, secondary source documents were identified by manual review of reference lists, review articles and guidelines. The search was limited to humans and adults (18+ years).